The Influence of CSR, AQ and Firm Size towards Tax Aggressiveness (Empirical Study on Mining Sector Coal and Metals and Minerals Sub-Sector listed on the Indonesia Stock Exchange for the 2014-2017) - Mulyati, Yati; Siagian, Fina; Putri, Nofianti Eka; Avianti, Farelin; Agustina, Belia Rizki; Rangel, Fernanda Junior (CENTRAL ASIA AND THE CAUCASUS, 2022)
In the last 5 years the realization of tax revenue has never reached the target. One of the causes of not achieving the tax revenue target is because there are companies that carry out tax aggressiveness, this is evidenced by the low ETR value of the company. This study aims to determine the effect of CSR, Audit Quality, Firm Size on Tax Aggressiveness. The sample of this research are from the financial report companies in mining sector, coal sub-sector and other metals and minerals sub- sectors listed on the Stock Market in Indonesia, period 2014-2017. With purposive sampling method, they where 44 samples were obtained. Data analysis in this study uses multiple linear regression analysis and is processed using Eviews 11. The results of the study prove that CSR, Audit Quality has an influence on Tax Aggressiveness, while company size has no effect on Tax Aggressiveness.